Essentials of epidemiology in public health - Aschengrau, Ann (Jones & Bartlett Learning, 2014)
"Tested in the authors' courses at Boston University and Harvard University, this Third Edition combines theory and practice in presenting traditional and new epidemiologic concepts. Broad in scope, the text opens with five chapters covering the basic epidemiologic concepts and data sources. A major emphasis is placed on study design, with separate chapters devoted to each of the three main analytic designs: experimental, cohort, and case-control studies. Full chapters on bias, confounding, and random error, including the role of statistics in epidemiology, ensure that students are well-equipped with the necessary information to interpret the results of epidemiologic studies. An entire chapter is also devoted to the concept of effect measure modification, an often-neglected topic in introductory textbooks. Up-to-date examples from the epidemiologic literature on diseases of public health importance are provided throughout the book"--